Virtual prototyping and analysis of functional tasks for hand rehabilitation - Chooi, Tuck You. (2009)
Robot-aided therapy is currently at the forefront of emerging field of rehabilitation. Robot-aided therapy devices assist patients in performing repetitive functional tasks and provide feedback on progress of patient to therapists concurrently. They have shown to be capable of improving performance of motor functioning and functional ability of impaired limbs caused by physical traumas such as stroke and spinal cord injury significantly. Many studies on rehabilitation have been carried out extensively worldwide but limited researches are done on hand rehabilitation. The main goal of this project is to perform and analyze simulations of five functional hand tasks using software MSC.ADAMS, namely the Cylindrical Grip, Pulp-to-Pulp Pinch, Lateral Pinch, 5-Pulp Pinch and Tripod Pinch. A 23-Degrees-of-Freedom (DOFs) virtual hand was modeled based on skeletal anatomy of realistic human hand using Solidworks. It is constituted by 22 articulated rigid bodies, representing finger bones, palm and forearm connected by rotational joints. Functional tasks were carried out by a normal male hand and recorded from top and side using digital video cameras. For each task, the animation data was acquired using simple motion-capture technique to measure angle variation of finger joints. In order to establish motion in ADAMS/View, a hand skeleton was required and built using rigid links. Parts of hand model were imported into ADAMS/View separately and attached to respective rigid links of skeleton. The animation data obtained previously was mapped onto joints of skeleton so that it performs exactly the same motion as human hand. The results show relatively good simulations of the functional tasks. It can be concluded that the simulation of Lateral Pinch fits the realistic hand motion most. The analyses of animation data and simulations can provide useful information towards the design and control applications of hand rehabilitation device which is in development currently.